Medium-density particleboards from rice husks and soybean protein concentrate - Leiva, Pablo (2007)
Rice husks are a valuable agricultural residue produced worldwide with potential applications as a wood substitute in particleboard manufacturing. In this work, the feasibility of producing medium-density particleboards based on waste rice husks bonded with environmentally friendly adhesives from soybean protein concentrate was analyzed. The mechanical properties, internal bond strength, and water resistance of the obtained panels bonded with the homemade soybean protein concentrate adhesives were compared to those of boards glued with commercial adhesives such as phenol-formaldehyde and urea-formaldehyde resins. An alkaline treatment improved the gluing ability of the soybean protein concentrate. The mechanical properties of the alkali-treated soybean protein concentrate were comparable to those determined for panels with urea-formaldehyde. The lower water resistance of the alkali-treated soybean protein concentrate particleboards, compared with that of the formaldehyde-based resins, was counterbalanced by the advantage of being more environmentally sound, which makes them suitable for applications for which the requirements for water resistance are not stringent.